RESPON PERTUMBUHAN DAN HASIL TANAMAN SELEDRI AKIBAT PEMBERIAN BOKASHI KAYAMBANG DAN ABU DI TANAH GAMBUT - Kresnatita S (Fakultas Pertanian Universitas Palangka Raya, 2017)
Application of kayambang bokashi (Salvinia molesta) and ash in peatland was a way to improve the environment of growth. Bokashi was used as fertilizer to produce variety of advantageous microbe population in soil so the growth of disadvantageous pathogens were inhibited, and also to increase the nutrient availability. Ash contain few essential nutrients for growth, development, and yield of plant. Application of ash in peatland was profitable to increase soil pH, add Ca and Mg, enchance the availability of P and Mo, reduce the toxication of Fe, Mn and Al, also to improve the existence of microorganisms in soil. The use of burnt ash of plant litter combustion in agriculture have been performed, whether to neutralize the soil acidity or as fertilizer. The aim of this study was to know the respond of celery growth and yield in peatland by giving kayambang bokashi and ash treatment. This study was performed for 4 months in Jl. Doho Kalampangan Village, Sabangau Districts, Palangka Raya City. This study used Factorial of Completely Random Design with 2 treatment factors. First factor was kayambang bokashi treatment (K) divided into 5 treatment levels, those were K0= without bokashi ; K1= 10 t.ha?1 (141 g.polybag) ; K2= 20 t.ha?1 (282 g.polybag) ; K3= 30 t.ha?1 (423 g.polybag) and K4= 40 t.ha?1 (564 g.polybag),wereas the second factor was ash treatment (B) divided into 4 treatment levels,those were B0 = without ash ; B1 = Ash 10 t.ha?1 (141 g.polybag-1) ; B2= Ash 20 t.ha?1 (282 g.polybag-1) ; B3= Ash 30 t.ha?1 (423 g.polybag-1) and B4= Ash 40 t.ha?1 (564 g.polybag). The result of this study showed that there were interaction between treatment of kayambang bokashi and ash on growth parameter of plant height aged 10 and 12 weeks after planting, number of leaves aged 8, 10, and 12 weeks after planting, also the fresh weight of root at harvest. There was significant difference of plant height parameter aged 2, 4, 6, and weeks after plantng, also fresh weight of stover in consequence of single treatment of kayambang bokashi and ash. There was significant difference of leaves number parameter aged 4 and 6 weeks after planting in consequence of single treatment of kayambang bokashi. There was no significant difference of celery’s number of leaves in 2 weeks after planting. The best treatment was application of kayambang bokashi dose of 40 t.ha?1 and ash at dose of 30 t.ha?1 (K4B3)